Preparation methods and applications of large-area "Janus" MoSSe two-dimensional nanosheets or MoSSe / MoS2 heterostructures
Patent Information
- Application Number
- CN202411152171.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-21
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-08-21
AI Technical Summary
Existing technologies make it difficult to prepare "Janus" MoSSe two-dimensional nanosheets or MoSSe/MoS2 heterostructures in large areas, with high yield and low cost. Furthermore, traditional methods are complex, costly, and can impair sample performance.
A two-stage atmospheric pressure chemical vapor deposition method was adopted. By controlling factors such as growth temperature, time and selenium powder quality, and using argon and hydrogen, the controllable growth of large-area "Janus" MoSSe two-dimensional nanosheets or MoSSe/MoS2 heterostructures was achieved, avoiding the use of hydrogen plasma and catalysts and simplifying the process.
It has enabled the controllable growth of high-quality, large-area Janus-like MoSSe two-dimensional nanosheets or MoSSe/MoS2 heterostructures, reducing fabrication costs, simplifying processes, and making them suitable for the fabrication of nonlinear optical, optoelectronic and other devices, thus providing the possibility of large-scale production.
Smart Images

Figure CN118992990B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of MoSSe nanomaterials technology, specifically to the preparation method and application of large-area "Janus" MoSSe two-dimensional nanosheets or MoSSe / MoS2 heterostructures. Background Technology
[0002] Since graphene was first experimentally prepared, it has been a research hotspot due to its unique physical properties. Its ultra-high carrier mobility, good mechanical flexibility and transparency make it have great application potential in transparent electrodes, field-effect transistors (FETs), gas sensing, wearable devices and other fields. However, the zero band gap of graphene limits its application in optoelectronic devices. In contrast, two-dimensional transition metal chalcogenides (TMDCs) such as molybdenum disulfide (MoS2), tungsten disulfide (WS2) and molybdenum diselenide (MoSe2) have great advantages in optoelectronic devices due to their tunable band gaps. This makes them complementary two-dimensional materials to graphene and widely used in optoelectronic devices such as photocatalysis, FETs and solar cells.
[0003] Beyond traditional 2D materials such as graphene and TMDCs, "Janus" TMDCs, as an emerging two-dimensional material, differ from MoS₂ with its randomly arranged S and Se atoms. x Se 2-x Instead of being an alloy, it consists of different types of chalcogenide elements flanking the transition metal atoms. This unique structure breaks the out-of-plane mirror symmetry of traditional TMDCs, generating a large number of vertical dipoles. For example, in monolayer "Janus" MoSSe, the molybdenum atoms in the middle are covalently bonded to the selenium atoms on the top layer and the sulfur atoms on the bottom layer. Previous theoretical calculations have demonstrated that "Janus" MoSSe possesses many unique physical properties, such as an ultra-high Curie temperature, ferromagnetic properties at room temperature, spin splitting, piezoelectricity, and various optical properties based on "Janus" MoSSe heterostructures. These novel properties inspire continuous exploration, making "Janus" TMDCs a research hotspot in the field of two-dimensional materials since their first successful fabrication.
[0004] However, the preparation method of "Janus" MoSSe differs from that of traditional TMDCs. Current experimental methods involve treating a monolayer of MoS2 with hydrogen plasma, causing H atoms to replace the S atoms on the top layer of MoS2, forming MoSH. This is followed by high-temperature chemical vapor deposition to selenize the sample, replacing the H atoms on the top layer of MoSH with Se atoms, successfully preparing MoSSe. However, this method is complex, costly, and can damage the sample, thus reducing device performance. Summary of the Invention
[0005] To address the technical challenge of achieving large-area, high-yield, and low-cost controllable fabrication of Janus-like MoSSe two-dimensional nanosheets, this invention provides a method and applications for the fabrication of large-area Janus-like MoSSe two-dimensional nanosheets or MoSSe / MoS2 heterojunctions. Based on a two-stage atmospheric pressure chemical vapor deposition method, this invention achieves controllable fabrication of large-area, high-yield Janus-like MoSSe two-dimensional nanosheets or MoSSe / MoS2 heterojunctions by controlling key influencing factors such as growth temperature, growth time, and selenium powder quality. This method offers low-cost fabrication, and the fabricated Janus-like MoSSe two-dimensional nanosheets or MoSSe / MoS2 heterojunctions show great application potential in piezoelectric properties, chemical hydrogen evolution, and nonlinear optics. This invention opens a new avenue for the controllable growth of Janus-like TMDCs two-dimensional semiconductors, providing experimental and theoretical support for their optoelectronic device applications and large-scale production.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0007] The preparation method of large-area "Janus" MoSSe two-dimensional nanosheets or MoSSe / MoS2 heterostructures includes the following steps:
[0008] S1. Clean the soda-lime glass substrate in deionized water to remove surface impurities;
[0009] S2. Oxidize the molybdenum foil in air to obtain molybdenum trioxide foil, fold the molybdenum trioxide foil into a bridge shape and place it on top of the soda-lime glass obtained in S1, then place it on a graphite sheet and push it to the heating center of the horizontal tube furnace.
[0010] S3. Based on the direction of airflow from upstream to downstream, place the quartz boat containing sulfur powder at an upstream position 25-29 cm away from the substrate, and place another quartz boat containing selenium powder in the room temperature area of the upstream tube opening of the tube furnace before growth.
[0011] S4. Open the gas valve and use argon to clean the furnace. After cleaning, continue to introduce argon throughout the growth process.
[0012] S5. Set the heating program so that the heating center is heated within 20 to 30 minutes and maintained at a growth temperature of 600 to 900°C for 8 to 15 minutes for the first stage of growth;
[0013] S6. After the first stage of growth is completed, open the hydrogen valve, introduce hydrogen into the tube, and use the magnetic suction device to push the quartz boat containing selenium powder from the upstream room temperature zone to the upstream position of the heating zone. Continue to maintain the growth temperature of the first stage for 4 to 25 minutes to carry out the second stage of growth.
[0014] S7. After growth is complete, allow the tube furnace to cool naturally to room temperature to obtain large-area "Janus" MoSSe two-dimensional nanosheets or MoSSe / MoS2 heterostructures.
[0015] Furthermore, it also includes closing the argon gas valve after the growth process is complete.
[0016] Furthermore, in S2, the oxidation temperature of the molybdenum foil is 440 ~ 460℃, and the oxidation time is 5 ~ 10 minutes.
[0017] Furthermore, in S3, the mass ratio of sulfur powder to selenium powder is 150~250:100~300, such as 150~250mg of sulfur powder and 100~300mg of selenium powder.
[0018] Furthermore, in S4, the argon flow rate is 80 ~ 120 sccm.
[0019] Furthermore, in S5, the growth temperature for the first stage is preferably 700~800℃.
[0020] Furthermore, in S6, the hydrogen flow rate is 5 ~ 15 sccm.
[0021] Furthermore, in S6, the quartz boat containing selenium powder is pushed to a distance of 24 to 26 cm from the heating center.
[0022] Furthermore, in S6, the growth time for the second stage is preferably 6 to 20 minutes.
[0023] The large-area "Janus" MoSSe two-dimensional nanosheets or MoSSe / MoS2 heterojunctions obtained by the above preparation method have excellent performance when applied to the fabrication of nonlinear optical, optoelectronic or valley electronic devices.
[0024] Compared with the prior art, the present invention has the following advantages: (1) The present invention adopts a two-stage growth strategy and obtains “Janus” MoSSe material by precisely controlling each process parameter (the material is characterized by the upper layer being all Se atoms and the lower layer being all S atoms). The present invention can achieve precise control of the replacement of all S atoms in the upper layer of the original MoS2 with Se atoms, and can ensure that the lower layer S atoms are not replaced, thereby finally obtaining the target product.
[0025] (2) The present invention uses atmospheric pressure chemical vapor deposition method. Due to the mismatch of the thermal expansion coefficients of MoS2 and the substrate, MoS2 will generate a certain degree of strain during the growth process. The strain introduced in MoS2 can effectively reduce the energy required for Se atoms to replace the top S atoms of MoS2 in the second stage, and further induce the controllable growth of the "Janus" MoSSe nanostructure.
[0026] (3) This invention does not require auxiliary devices such as hydrogen plasma or pulsed laser. It effectively reduces the material preparation cost and simplifies the process and technology by changing the properties of the material itself.
[0027] (4) This invention does not require the addition of chloride, hydroxide or other related catalysts during the experiment. The introduction of impurity elements is avoided throughout the experiment, thus achieving the controllable growth of high-quality, large-area “Janus” MoSSe two-dimensional nanosheets or MoSSe / MoS2 heterostructures.
[0028] (5) Compared with mechanical exfoliation and other methods, the chemical vapor deposition method of this invention can control key experimental parameters such as growth time, and can realize the mass production of large-area single-layer "Janus" MoSSe two-dimensional nanosheets or MoSSe / MoS2 heterojunctions.
[0029] (6) The material obtained by this invention is a two-dimensional nanosheet of "Janus" MoSSe or a MoSSe / MoS2 heterojunction, which can be directly characterized by Raman spectroscopy, photoluminescence spectroscopy, atomic force microscopy, XPS and nonlinear optics (second harmonics), and provides a feasible path for the subsequent fabrication of related micro and nano devices.
[0030] (7) The Janus-like MoSSe nanosheets and MoSSe / MoS2 vertical heterojunctions prepared by this invention can be transferred to other substrates for application research such as optoelectronic devices. Attached Figure Description
[0031] Figure 1 This is a schematic diagram illustrating the growth principle of the "Janus" MoSSe two-dimensional nanosheets prepared in Example 1.
[0032] Figure 2 This is a digital photograph of the Janus-like MoSSe two-dimensional nanosheets obtained in Example 1 grown on a soda-lime glass substrate.
[0033] Figure 3 The optical microscopy characterization results of the Janus-like MoSSe two-dimensional nanosheets obtained in Example 1 are shown.
[0034] Figure 4 The Raman spectral characterization results are for the Janus-like MoSSe two-dimensional nanosheets obtained in Example 1.
[0035] Figure 5 The results are Raman surface scanning characterization of the Janus-like MoSSe two-dimensional nanosheets obtained in Example 1.
[0036] Figure 6 The photoluminescence spectrum characterization results of the "Janus" MoSSe two-dimensional nanosheets obtained in Example 1 are shown.
[0037] Figure 7 The atomic force microscopy characterization results of the "Janus" MoSSe two-dimensional nanosheets obtained in Example 1 are shown.
[0038] Figure 8 XPS characterization results of Mo 3d orbitals in the Janus-like MoSSe two-dimensional nanosheets obtained in Example 1.
[0039] Figure 9 XPS characterization results of the S 2p / Se 3p orbitals of the Janus MoSSe two-dimensional nanosheets obtained in Example 1.
[0040] Figure 10 XPS characterization results of the Se 3d orbitals of the Janus MoSSe two-dimensional nanosheets obtained in Example 1.
[0041] Figure 11 The optical microscopy characterization results are for the MoSSe / MoS2 vertical heterojunction obtained in Example 2.
[0042] Figure 12 The results are Raman spectroscopic characterizations of the MoSSe / MoS2 vertical heterojunction obtained in Example 2.
[0043] Figure 13 The results are Raman surface scanning characterization of the MoSSe / MoS2 vertical heterojunction obtained in Example 2.
[0044] Figure 14 The results show the second harmonic spectrum characterization of the MoSSe / MoS2 vertical heterojunction obtained in Example 2.
[0045] Figure 15 The relationship between the second harmonic intensity of the AA-stacked MoSSe / MoS2 vertical heterojunction obtained in Example 2 and the pump power is shown.
[0046] Figure 16 The relationship between the second harmonic intensity of the AB stacked MoSSe / MoS2 vertical heterojunction obtained in Example 2 and the pump power is shown.
[0047] Figure 17 The second harmonic intensity of the monolayer "Janus" MoSSe nanosheets obtained in Example 2 varies with pump power. Detailed Implementation
[0048] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments, but the present invention is not limited thereto.
[0049] Example 1
[0050] A 2.5 × 2 cm soda-lime glass substrate was used. The substrate was first cleaned in deionized water to remove surface impurities. Molybdenum foil was oxidized in air at 470°C for 5 minutes to obtain molybdenum trioxide foil. This molybdenum trioxide foil was folded into a bridge shape and placed on top of the soda-lime glass, then placed on a graphite sheet and pushed to the center of the horizontal tube furnace heating zone. Following the upstream-to-downstream airflow direction, a quartz boat containing 200 mg of sulfur powder was placed upstream of the heating zone of the tube furnace, with the distance between the quartz boat and the heating center being 27 cm. Another quartz boat containing 200 mg of selenium powder was placed at room temperature near the upstream inlet of the tube furnace before growth. The gas valve was then opened, and the furnace was purged with 200 sccm of argon gas for 15 minutes. After purging, argon gas was continuously introduced throughout the growth process at a flow rate of 100 sccm. The next step involved setting a heating program to raise the temperature of the heating center to the growth temperature of 750°C within 25 minutes and maintain this temperature for 10 minutes for the first stage of molybdenum disulfide nanostructure growth. After the first stage of growth, hydrogen gas was introduced into the tube at a flow rate of 10 sccm. Simultaneously, a quartz boat containing selenium powder was pushed from the upstream room temperature zone to the upstream of the heating zone using a magnetic attraction device, with the boat 24 cm away from the heating center. The second stage of growth was carried out at the growth temperature of 750°C for another 20 minutes, yielding "Janus" MoSSe two-dimensional nanosheets. After growth, the tube furnace was allowed to cool naturally to room temperature before the gas valve was closed, and the sample was removed from the furnace. A schematic diagram of the growth principle is shown below. Figure 1 As shown.
[0051] Digital images of large-area "Janus" MoSSe two-dimensional nanosheets obtained from the growth, such as Figure 2 As shown. The large-area "Janus" MoSSe two-dimensional nanosheets obtained in Example 1 were characterized by optical microscopy, Raman spectroscopy, Raman surface scanning, photoluminescence spectroscopy, atomic force microscopy, and XPS. The results are as follows. Figures 1 to 10 As shown in the figure. Optical microscopy characterization reveals that the prepared "Janus" MoSSe two-dimensional nanosheets are triangular in structure with a smooth and flat surface, indicating high sample quality. Raman spectroscopy data shows that the sample exhibits high density at 288 cm⁻¹. -1 and 355 cm -1 Two typical characteristic peaks of the "Janus" MoSSe two-dimensional nanosheets were observed, namely the A peak of "Janus" MoSSe. 1g and E 1 2g The peak is consistent with previously reported data. Furthermore, the sample underwent A... 1gRaman surface scanning characterization of the peaks showed that the nanosheets exhibited uniform signal intensity, confirming the good uniformity of the "Janus" MoSSe two-dimensional nanosheets. Photoluminescence spectroscopy revealed a characteristic peak at 1.71 eV, consistent with reported data. Atomic force microscopy characterization of the "Janus" MoSSe two-dimensional nanosheets showed a thickness of 0.9 nm, indicating that the sample was a monolayer. XPS characterization revealed that the orbital fitting curves for Mo 3d, S 2p / Se 3p, and Se 3d were consistent with their standard binding energy fitting curves, further confirming the successful synthesis of large-area "Janus" MoSSe two-dimensional nanosheets.
[0052] Due to the mismatch in thermal expansion coefficients between monolayer MoS2 and the soda-lime glass substrate, a certain degree of strain will occur during the growth process. This strain can reduce the energy required for the sulfur atoms on the upper layer of MoS2 to be replaced by selenium atoms, thereby further and more effectively inducing the growth of "Janus" MoSSe two-dimensional nanosheets. This invention is based on a two-stage atmospheric pressure chemical vapor deposition method, which effectively introduces strain in the second stage, thus successfully achieving the controllable growth of large-area monolayer "Janus" MoSSe two-dimensional nanosheets without the need for external high-energy intervention.
[0053] Example 2
[0054] Maintaining the growth process of Example 1, by shortening the growth time of the second stage to 10 minutes while keeping other experimental conditions unchanged, controllable growth of MoSSe / MoS2 heterojunctions can be achieved. The MoSSe / MoS2 vertical heterojunction obtained in Example 2 was characterized by optical microscopy, and the results are as follows: Figure 11 As shown. Raman spectroscopy characterization data reveals that the sample at 288 cm⁻¹... -1 355 cm -1 383cm -1 and 402cm -1 Four typical characteristic peaks appeared near the location, corresponding to the A peaks of the Janus MoSSe. 1g and E 1 2g Peak and E of MoS2 1 2g and A 1g The peak indicates the successful synthesis of the MoSSe / MoS2 vertical heterostructure, such as Figure 12 As shown. Furthermore, the sample underwent A244-dimer oxidation using Janus MoSSe. 1g Raman surface scanning characterization of the peaks revealed different signal intensities between the MoSSe / MoS2 vertical heterostructure and the bottom monolayer "Janus" MoSSe nanosheets. Figure 13 As shown. Figure 14Second harmonic (HHM) spectroscopic characterization tests were performed on AA-stacked, AB-stacked MoSSe / MoS2 vertical heterojunctions and monolayer "Janus" MoSSe nanosheets, respectively. The results showed that the AA-stacked MoSSe / MoS2 vertical heterojunction had the highest signal intensity, approximately four times that of the AB-stacked MoSSe / MoS2 vertical heterojunction. The relationships between the HHM intensity of the AA-stacked, AB-stacked MoSSe / MoS2 vertical heterojunctions and the monolayer, and the pump power are shown below. Figure 15 As shown in Figures 16 and 17, the fitting slopes are close to 2, further demonstrating the excellent application prospects of the "Janus" MoSSe two-dimensional nanosheets and its MoSSe / MoS2 heterostructure in the field of nonlinear optics.
Claims
1. A method for preparing large-area "Janus" MoSSe two-dimensional nanosheets, characterized in that, Includes the following steps: S1. Clean the soda-lime glass substrate in deionized water to remove surface impurities; S2. Oxidize the molybdenum foil in air to obtain molybdenum trioxide foil, fold the molybdenum trioxide foil into a bridge shape and place it on top of the soda-lime glass obtained in S1, then place it on a graphite sheet and push it to the heating center of the horizontal tube furnace. S3. Based on the direction of airflow from upstream to downstream, place the quartz boat containing sulfur powder at an upstream position 25-29 cm away from the substrate, and place another quartz boat containing selenium powder in the room temperature area of the upstream tube opening of the tube furnace before growth. S4. Open the gas valve and use argon to clean the furnace. After cleaning, continue to introduce argon throughout the growth process. S5. Set the heating program so that the heating center is heated within 20 to 30 minutes and maintained at a growth temperature of 600 to 900°C for 8 to 15 minutes for the first stage of growth; S6. After the first stage of growth is completed, open the hydrogen valve, introduce hydrogen into the tube, and use the magnetic suction device to push the quartz boat containing selenium powder from the upstream room temperature zone to the upstream position of the heating zone. Continue to maintain the growth temperature of the first stage for 20-25 minutes to carry out the second stage of growth. S7. After growth is complete, allow the tube furnace to cool naturally to room temperature to obtain large-area "Janus" MoSSe two-dimensional nanosheets.
2. The method for preparing large-area "Janus" MoSSe two-dimensional nanosheets according to claim 1, characterized in that, In S2, the oxidation temperature of the molybdenum foil is 440 ~ 460℃, and the oxidation time is 5 ~ 10 minutes.
3. The method for preparing large-area "Janus" MoSSe two-dimensional nanosheets according to claim 1, characterized in that, In S3, the mass ratio of sulfur powder to selenium powder is 150 ~ 250: 100 ~ 300.
4. The method for preparing large-area "Janus" MoSSe two-dimensional nanosheets according to claim 1, characterized in that, In S4, the argon flow rate is 80 ~ 120 sccm.
5. The method for preparing large-area "Janus" MoSSe two-dimensional nanosheets according to claim 1, characterized in that, In S5, the growth temperature for the first stage is 700 ~ 800℃.
6. The method for preparing large-area "Janus" MoSSe two-dimensional nanosheets according to claim 1, characterized in that, In S6, the hydrogen flow rate is 5 ~ 15 sccm.
7. The method for preparing large-area "Janus" MoSSe two-dimensional nanosheets according to claim 1, characterized in that, In S6, the quartz boat containing selenium powder is pushed to a distance of 24 to 26 cm from the heating center.
8. A method for preparing a MoSSe / MoS2 heterojunction, characterized by comprising the following steps: S1. Clean the soda-lime glass substrate in deionized water to remove surface impurities; S2. Oxidize the molybdenum foil in air to obtain molybdenum trioxide foil, fold the molybdenum trioxide foil into a bridge shape and place it on top of the soda-lime glass obtained in S1, then place it on a graphite sheet and push it to the heating center of the horizontal tube furnace. S3. Based on the direction of airflow from upstream to downstream, place the quartz boat containing sulfur powder at an upstream position 25-29 cm away from the substrate, and place another quartz boat containing selenium powder in the room temperature area of the upstream tube opening of the tube furnace before growth. S4. Open the gas valve and use argon to clean the furnace. After cleaning, continue to introduce argon throughout the growth process. S5. Set the heating program so that the heating center is heated within 20 to 30 minutes and maintained at a growth temperature of 600 to 900°C for 8 to 15 minutes for the first stage of growth; S6. After the first stage of growth is completed, open the hydrogen valve, introduce hydrogen into the tube, and use the magnetic suction device to push the quartz boat containing selenium powder from the upstream room temperature zone to the upstream position of the heating zone. Continue to maintain the growth temperature of the first stage for 4 to 10 minutes to carry out the second stage of growth. S7. After growth is complete, the tube furnace is allowed to cool naturally to room temperature to obtain the MoSSe / MoS2 heterojunction.
9. The method for preparing a MoSSe / MoS2 heterojunction according to claim 8, characterized in that, In S2, the oxidation temperature of the molybdenum foil is 440 ~ 460℃, and the oxidation time is 5 ~ 10 minutes.
10. The method for preparing a MoSSe / MoS2 heterojunction according to claim 8, characterized in that, In S3, the mass ratio of sulfur powder to selenium powder is 150 ~ 250: 100 ~ 300.
11. The method for preparing a MoSSe / MoS2 heterojunction according to claim 8, characterized in that, In S4, the argon flow rate is 80 ~ 120 sccm.
12. The method for preparing a MoSSe / MoS2 heterojunction according to claim 8, characterized in that, In S5, the growth temperature for the first stage is 700 ~ 800℃.
13. The method for preparing a MoSSe / MoS2 heterojunction according to claim 8, characterized in that, In S6, the hydrogen flow rate is 5 ~ 15 sccm.
14. The method for preparing a MoSSe / MoS2 heterojunction according to claim 8, characterized in that, In S6, the quartz boat containing selenium powder is pushed to a distance of 24 to 26 cm from the heating center.
Citation Information
Patent Citations
Design method of wearable two-dimensional asymmetric material with high thermoelectric conversion efficiency
CN114462178A
CZTS solar cell and method of preparing thereof
KR102070852B1
